Learning more and spending less with neglected laboratory parameters: the paradigmatic case of red blood cell distribution width. - Lippi, Giuseppe; Mattiuzzi, Camilla; Cervellin, Gianfranco (Acta Biomedica Atenei Parmensis, 2017)
Due to increasing shortage of public healthcare resources in many countries around the globe, the use of simple, rapid and inexpensive laboratory parameters may be seen as a valuable aid for preliminary and cost-effective risk stratification of patients. Anisocytosis, conventionally measured by hematologic analyzers as the red blood cell distribution width (RDW), is an index of the heterogeneity of erythrocytes volumes. Several lines of evidence now attest that increased RDW values are commonplace in patients with many disorders, especially in those with the most prevalent conditions such as cardiovascular disease, diabetes, cancer and infections. Although the nature of this association remains to be definitely disclosed, what is strongly emerging from the recent scientific research is that the RDW should now be regarded as a “non” innocent bystander, wherein anisocytosis may be an active player in the pathogenesis of many pathologies. Therefore, major attention should be placed on this inexpensive but clinically meaningful parameter. The recent finding that dynamic changes of RDW are strongly predictors of mortality also suggests that continuous monitoring of anisocytosis may be an ancillary useful tool for establishing the effectiveness of managed care, as well as for deciding whether or not the overall clinical status is improving.